Safety and Efficacy of Low Molecular Weight Heparin for Thromboprophylaxis in the Elderly: A Network Meta-Analysis of Randomized Clinical Trials - Yang, Hui-qin; Liu, Man-cang; Yin, Wen-jun; Zhou, Ling-yun; Zuo, Xiao-cong (Frontiers in Pharmacology, 2021)
Background: Given their changing pathophysiology, elderly patients carry a high-risk of embolism and bleeding events; hence, use of appropriate anticoagulants is very important. Low molecular weight heparin (LMWHs) is one of the most widely used anticoagulants, although LMWHs differ in their anti-Xa, antithrombin, and anticoagulant activities. To date, no study has directly compared the safety and efficacy of different LMWHs in the elderly. We aimed to compare such differences by conducting a network meta-analysis. Methods: We searched the Pubmed, Embase, and Cochrane databases for randomized controlled trials (RCTs) of LMWHs that included patients ≥60 years old up to July 22, 2020. Safety outcomes included venous thromboembolism(VTE) or VTE-related death, deep thrombus embolism, and pulmonary embolism. Safety outcomes were clinically relevant bleeding, major bleeding, minor bleeding, and all-cause death. We calculated relative ratios (RR) and 95% confidence intervals (CI) for all outcomes. And the cumulative ranking probabilities (SUCRA) were conducted to rank the comparative effects and safety of all LMWHs. Results: We included 27 RCTs (30441 elderly), comprising of 5 LMWHs. LMWH was more effective than placebo in preventing VTE or VTE-related death (RR 0.36, 95%CI 0.25-0.53), but less effective than novel oral anticoagulant (RR 1.59, 95%CI 1.33-1.91), and safer than acenocoumarol regarding risk of clinically relevant bleeding (RR 0.67, 95%CI 0.49-0.90). However, indirect comparison of efficacy and safety of the 5 LMWHs showed no significant difference in our network analysis, and the subgroup analyses (such as in patients with deep venous thrombosis, cardiac disease, or age >65 years old) supported the results. The SUCRA showed that tinzaparin performed best in preventing VTE or VTE-related death (SUCRA 68.8%, cumulative probability 42.3%) and all-cause death (SUCRA 84.2%, cumulative probability 40.7%), while nadroparin was predominant in decreasing the risk of clinically relevant bleeding (SUCRA 84.8%, cumulative probability 77.0%). Conclusions: On present evidence, there are no significant differences in the efficacy and safety of different LMWHs for the elderly. According to the rank probability analysis, nadroparin seems to be safer for the elderly with a high risk of bleeding, while tinzaparin is more effective for those with low bleeding risk.